Mitigation and adaptation to climate change under agroforestry systems in cocoa production in the Amazon and Atlantic Forest biomes in Brazil - Souza, Romelia (2025)
In participation with the Inter-American Institute for Cooperation on Agriculture (IICA), Ministry of Agriculture, Livestock and Food Supply (MAPA) and Green Climate Fund (GCF)